Social media addiction and its effect on academic performance in Bangladeshi students - Bushra, Rabeya; Ashimi, Tijani Ahmad; Khan, Khan Md Abdus Subhan; Azad, Abul Kalam Azad (Common Ground Research Networks, 2025)
Abstract Focusing on both its advantages and drawbacks, this study looks at how social media use affects the academic performance of Bangladeshi university students. As digital platforms increasingly become part of daily life, social media has transformed how students learn, interact with peers, and manage their academic responsibilities. On the other hand, too much use has been connected to several academic difficulties, including poor concentration, poor time management, and declining academic performance. Using a structured questionnaire, data were gathered from 225 university students in Dhaka, Bangladesh, applying a quantitative research design. To assess the relationship between social media participation and academic performance, statistical analyses including correlation and comparative tests were done. The results show a clear negative correlation between students' capacity to concentrate, finish homework, and control academic stress and their use of social media. Emphasising the need for customised intervention strategies, gender-based changes in the effect of social media were also found. Social media presents chances for academic cooperation, resource sharing, and skill development, but overuse of it fuels academic disengagement and stress. These findings highlight the need for institutional policies, digital literacy campaigns, and moderation in social media use in order to minimise its negative academic consequences. Encouraging responsible social media use to maximise academic success, the study offers an insightful analysis for institutions, legislators, and students. Future studies should investigate long-term consequences and the influence of newly developing social media platforms on academic practices.